Reactivity of Rheumatic Fever and Scarlet Fever Patients' Sera with Group A Streptococcal M Protein, Cardiac Myosin, and Cardiac Tropomyosin: a Retrospective Study - Jones, Kevin F. (American Society for Microbiology, 2000)
Archived sera (collected in 1946) from acute rheumatic fever (ARF) and untreated scarlet fever and/or pharyngitis patients were reacted with streptococcal M protein, cardiac myosin, and cardiac tropomyosin. Except for very low levels to tropomyosin, antibodies to other antigens were not elevated in the sera of ARF patients relative to those of non-ARF patients, even though there was roughly equivalent exposure to group A streptococci. This suggests that antibodies to these molecules may not play a central role in the induction of ARF.